Neuroprotective effects of Ocimum basilicum L. var. thyrsiflora on scopolamine- induced non-spatial memory deficits in rats - Nor Syafinaz Yaakob; Seyed, Mohamed Ali; Manali Haniti Mohd-Zahid; Tee, Heng-Hui; Yap, Shu-Yun; Ho, Sek-Wen; Yusof Kamisah; Norazrina Azmi (Universiti Kebangsaan Malaysia, 2023)
Pharmacological studies indicated that Ocimum basilicum L. var. thyrsiflora has numerous therapeutic potentials. The aim of this study was to investigate the neuroprotective action of O. basilicum leaf extract against scopolamine-induced non-spatial memory deficits in rats and to determine the changes in mRNA expressions of genes implicated in cognition and neuroprotection. O. basilicum leaves were extracted with 80% ethanol and verified for the presence of rosmarinic acid using high performance liquid chromatography method. Male Wistar rats were treated orally with eitherO. basilicum or the positive control piracetam for 14 days prior to the injection of 0.5 mg/kg scopolamine on the day of the novel object discrimination (NOD) test. Hippocampi were collected at the end of the test. mRNA expression of nicotinic acetylcholine α7 subunit (NA7), muscarinic M1 receptor (M1), neuronal nitric oxide synthase (nNOS), and 5-hydroxytryptamine receptor 3A (HTR3A) genes in the hippocampi were analyzed using qPCR method. The presence of rosmarinic acid in the plant extract was detected at chromatogram peak of Rt=16.891. NOD test results indicated that the lower dose of O. basilicum (200 mg/kg) significantly (p<0.05) reversed scopolamine-induced memory deficits in rats similar to the effects of piracetam. In addition, O. basilicum at the same dose alleviated the increase in mRNA expressions of the NA7, M1, nNOS, and HTR3A genes induced by scopolamine. The present findings suggest that O. basilicum is potentially neuroprotective in preventing memory impairment through alleviation of scopolamine-induced changes in hippocampal mRNA expression implicated in cognition and neuroprotection.